DEVELOPMENT OF YOUTH'S CREATIVE ABILITIES SCHOOLCHILDREN BY BYOD TECHNOLOGY - Demchenko, Olena; Bondar, Yuliia; Shykyrynska, Oleksandra; Komarivska, Nadiia; Lyubchak, Lyudmila; Stakhova, Inna; Dabizha, Liudmyla (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Modernization of the modern primary education system of Ukraine is aimed at developing creative abilities of primary school students. Development of the creative abilities is one of the components of soft skills of an individual, they affect the successful establishment in society. A creative person is able to generate new ideas, think original, make non-standard decisions, confidently achieve their goals. Creativity is an integrative multicomponent quality that covers various areas of students’ activity. Due to the digitalization of the educational process, information and communication technologies are being rapidly implemented in primary school. Accordingly, the authors of the article analyzed the features of the use of innovative technology BYOD ("bring your own device") for the development of creative abilities of students, identified its positive aspects, outlined ways to use it by teachers. The purpose of the article is to reveal the educational potential of BYOD technology for the development of creative abilities of junior schoolchildren. An experimental study was conducted, the respondents of which were students of primary school in Vinnytsia region and determined the leading level of development of their creative abilities. The results of lessons observation in primary school on the use of innovative technologies for the formation of creative abilities of primary school students are analyzed. The results of the survey of primary school teachers on the use of innovative BYOD technology in the educational process are presented. It is proved that the use of smartphones in primary school lessons promotes the development of creative abilities of primary school children and their imagination, and change of the educational vector of primary school from reproductive learning to creative understanding of information and competent growth (formation of digital competence and organization of students’ independent research).